Acquisitions, productivity, and profitability: Evidence from the Japanese cotton spinning industry - Serguey Braguinsky; Atsushi Ohyama; Tetsuji Okazaki; Chad Syverson (National Bank of Belgium, 2014)
We explore how changes in ownership and managerial control affect the productivity and profitability of producers. Using detailed operational, financial, and ownership data from the Japanese cotton spinning industry at the turn of the last century, we find a more nuanced picture than the straightforward “higher productivity buys lower productivity” story commonly appealed to in the literature. Acquired firms' production facilities were not on average less physically productive than the plants of the acquiring firms before acquisition, conditional on operating. They were much less profitable, however, due to consistently higher inventory levels and lower capacity utilization—differences that reflected problems in managing the uncertainties of demand. When purchased by more profitable firms, these less profitable acquired plants saw drops in inventories and gains in capacity utilization that raised both their productivity and profitability levels, consistent with acquiring owner/managers spreading their better demand management abilities across the acquired capital.
Keywords: 330; Übernahme; Produktivität; Rentabilität; Baumwollindustrie; Geschichte; Theorie; Japan